Bioactive Materials for Soft Tissue Repair - Mazzoni, Elisa; Iaquinta, Maria Rosa; Lanzillotti, Carmen; Mazziotta, Chiara; Maritati, Martina; Montesi, Monica; Sprio, Simone; Tampieri, Anna; Tognon, Mauro; Martini, Fernanda (Frontiers in Bioengineering and Biotechnology, 2021)
Over the past decades, age-related pathologies have increased abreast the aging population worldwide. Aging has highlighted the need for intervention with biomaterials / scaffolds on human damaged tissues, which display high efficiency, effectively and in a limited period of time, for the regeneration of the body's tissue. Indeed, scaffolds can be used as templates for three-dimensional tissue growth in order to promote the tissue healing stimulating the body’s own regenerative mechanisms. In tissue engineering, several types of biomaterials are employed, such as bioceramics including calcium phosphates, bioactive glasses, and glass–ceramics. These scaffolds seem to have a high potential as biomaterials in regenerative medicine. In addition, in conjunction with other materials, such as polymers, ceramic scaffolds may be used to manufacture composite scaffolds characterized by high biocompatibility, mechanical efficiency and load-bearing capabilities that render these biomaterials suitable for tissue engineering. Usually, bioceramics have been used to repair hard tissues, such as bone and dental defects. More recently, in the field of soft tissue engineering, this form of scaffold has also shown promising applications. Indeed, soft tissues are continuously exposed to damages, such as burns or mechanical traumas, tumors and degenerative pathology, and, thereby, thousands of people need remedial interventions such as biomaterials-based therapies. It is known that scaffolds can affect the ability to bind, proliferate and differentiate cells similar to those of autologous tissues. Therefore, it is important to investigate the interaction between bioceramics and somatic/stem cells derived from soft tissues in order to promote tissue healing. Biomimetic scaffolds are frequently employed as drug-delivery system using several therapeutic molecules to increase their biological performance, leading to ultimate products with innovative functionalities. This review provides an overview of essential requirements for soft tissue engineering biomaterials. Data on recent progresses of porous bioceramics and composites for tissue repair are also presented.